Citrullination regulates the expression of insulin-like growth factor-binding protein 1 (IGFBP1) in ovine uterine luminal epithelial cells. Issue 1 (January 2017) - Young, Coleman H; Rothfuss, Heather M; Gard, Philip F; Muth, Aaron; Thompson, Paul R; Ashley, Ryan L; Cherrington, Brian D
Abstract : There are five peptidylarginine deiminase (PAD) isozymes designated as PADs 1, 2, 3, 4 and 6, and many are expressed in female reproductive tissues. These enzymes post-translationally convert positively charged arginine amino acids into neutral citrulline residues. Targets for PAD-catalyzed citrullination include arginine residues on histone tails, which results in chromatin decondensation and changes in gene expression. Some of the first studies examining PADs found that they are localized to rodent uterine epithelial cells. Despite these findings, the function of PAD-catalyzed citrullination in uterine epithelial cells is still unknown. To address this, we first examined PAD expression in uterine cross-sections from pregnant ewes on gestation day 25 (d25). Immunohistochemistry revealed that the levels of PADs 2 and 4 are robust in luminal and glandular epithelia compared with those of PADs 1 and 3. As PADs 2 and 4 have well-characterized roles in histone citrullination, we next hypothesized that PADs citrullinate histones in these uterine cells. Examination of caruncle lysates from pregnant ewes on gestation d25 and an ovine luminal epithelial (OLE) cell line shows that histone H3 arginine residues 2, 8, 17 and 26 are citrullinated, but histone H4 arginine 3 is not. Using a pan-PAD inhibitor, we next attenuated histone citrullination in OLE cells, which resulted in a significant decrease in the expression of insulin-like growth factor-binding protein 1 ( IGFBP1 ) mRNA. As IGFBP1 is important for the migration and attachment of the trophectoderm to uterine endometrium, our results suggest that PAD-catalyzed citrullination may be an important post-translational mechanism for the establishment of pregnancy in ewes.